BUILDING ORIENTATION EFFECTS ON HVAC ENERGY PERFORMANCE: EDUCATIONAL BUILDING ANALYSIS IN CHINA'S HOT-SUMMER-COLD-WINTER ZONE - Li, Rong; Shari, Zalina; Ab. Kadir, Mohd Zainal Abidin (Journal of Surveying, Construction and Property, 2025)
This study investigated the impact of building orientation on HVAC energy consumption in educational buildings within China's hot summer and cold winter (HSCW) climate zone. Through EnergyPlus simulations of a representative teaching building in Chongqing, this research analysed heating, cooling, and total HVAC energy consumption patterns across 24 different orientations. The results demonstrate that building orientation significantly influences energy performance, with the south-facing orientation (180°) achieving optimal energy efficiency at 58.55 kWh/m², while the west-facing orientation (270°) exhibits the highest consumption at 63.01 kWh/m², representing a 7.62% variation. The study reveals that maintaining the building orientation within ±15° of due south can effectively optimise year-round energy performance, particularly in regions with significant seasonal variations. Furthermore, the findings indicate distinct seasonal patterns, with south-facing orientations demonstrating superior winter performance through optimal solar gain while requiring careful solar control strategies during summer. This study provides quantitative evidence to support the development of specific orientation design guidelines for building energy standards, offering practical insights for architects and urban planners in creating energy-efficient educational facilities in HSCW climate zones.